What is the equation of the tangent line of #f(x)=sqrt((x-1)^3e^(2x) # at #x=2#?

Answer 1

#g (x)=5/2 e^2x -4e^2#

To solve this problem as presented, we must do the following:

(1)

#f (2)= sqrt ((2-1)^3e^(2*2)) = sqrt (e^4) = e^2#

(2)

#f (x)= sqrt ((x-1)^3e^(2x)) = e^x(x-1)^(3/2)#

Recall that the product rule states for

#a (x)=b (x)c (x) => a'=b'c+bc'#

Additionally, the chain rule states that given

#k (x)=m (n (x)), (dk)/dx = (dn)/dx*(dm)/(dn) #.

Here, we have the following:

#a (x) = f (x) = b (x)c (x)=e^x (x-1)^(3/2)#
#=> b (x) = e^x -> b'(x) = e^x#
#=> c (x) = k (x) = m (n (x)) = (x-1)^(3/2)#

where we take

#n (x)=(x-1) ->(dn)/dx = 1#
#m (n) = n^(3/2) -> (dm)/(dn) = 3/2 n^(1/2)#
#c'(x) = (dc)/dx = (dk)/dx = 3/2 (x-1)^(1/2)#
#f'(x) = e^x (x-1)^(1/2) + 3/2 (x-1)^(1/2) e^x#
#f'(2) = e^2 +3/2 e^2 = 5/2 e^2#
(3) We now find #g(x)#, which we define as being the tangent line at #x=2#. We use our slope from (2), our #f (2)# from (1), and our #x# from the problem to get...
#g(x) - e^2 = 5/2 e^2 (x-2) = 5/2 e^2x-4e^2 -> g (x)=5/2 e^2x -4e^2#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

The equation of the tangent line is

#y=5/2e^2x - 4e^2#

The equation of a line in the form

#y=mx+b#
contains a slope, #m# and a #y#-intercept #b#. We can obtain the slope from the equation by taking the derivative and substituting the #x# value of #2#. We can then solve for the #y#-intercept using the point #(2,f(2))#

Let's begin by getting the y-value of the point we want the line to go through:

#f(2) = sqrt((2-1)^3*e^(2*2))#
#f(2) = sqrt((1)^3*e^(4)) = e^2#
Next we need to take the derivative of #f(x)#, but first I'd like to distribute the square root over the factors inside it, just so I don't have to use the chain rule an extra time:
#f(x) = (x-1)^(3/2)*e^x#
#f'(x) = d/(dx)[(x-1)^(3/2)*e^x] #

Then we use the chain rule:

#f'(x) = [d/(dx) (x-1)^(3/2)] * e^x + (x-1)^(3/2) * [d/(dx)e^x]#
#f'(x) = 3/2 (x-1)^(1/2) * e^x + (x-1)^(3/2)*e^x#

solving for the slope at the point of interest:

#f'(2) = 3/2 (2-1)^(1/2) * e^2 + (2-1)^(3/2)*e^2#
#f'(2) = 3/2 e^2 + e^2 = 5/2e^2#
Now in our equation for the line at the point #(2,e^2)#:
#y = 5/2e^2x +b#
#e^2 = 5e^2 + b#
# => b=-4e^2#

finally the equation of the tangent line is

#y=5/2e^2x - 4e^2#

which we can graph to check our solution:

graph{(5(e^2)/2x-4e^2-y)(sqrt((x-1)^3e^(2x))-y)=0 [1 3 -20 20]}

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To find the equation of the tangent line of f(x) = sqrt((x-1)^3e^(2x)) at x = 2, we need to find the slope of the tangent line and a point on the line.

First, we find the derivative of f(x) using the chain rule and product rule. The derivative is given by:

f'(x) = (3(x-1)^2e^(2x) + 2(x-1)^3e^(2x))/(2sqrt((x-1)^3e^(2x)))

Next, we substitute x = 2 into f'(x) to find the slope of the tangent line:

f'(2) = (3(2-1)^2e^(22) + 2(2-1)^3e^(22))/(2sqrt((2-1)^3e^(2*2)))

Simplifying this expression gives us the slope of the tangent line.

Finally, we use the point-slope form of a line, y - y1 = m(x - x1), where (x1, y1) is a point on the line and m is the slope, to find the equation of the tangent line. We substitute the values of x1, y1, and m into the equation and simplify to obtain the final equation of the tangent line.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7